Surgical management of penile carcinoma in situ: results from an international collaborative study and review of the literature. (24th October 2017) - Chipollini, Juan; Yan, Sylvia; Ottenhof, Sarah R.; Zhu, Yao; Draeger, Désirée; Baumgarten, Adam S.; Tang, Dominic H.; Protzel, Chris; Ye, Ding‐wei; Hakenberg, Oliver W.; Horenblas, Simon; Watkin, Nicholas A.; et al.
Abstract : Objectives: To evaluate recurrence after penile‐sparing surgery (PSS) in the management of carcinoma in situ (CIS) of the penis in a large multicentre cohort of patients. Patients and Methods: We identified consecutive patients from five major academic centres, treated between June 1986 and November 2014, who underwent PSS for pathologically proven penile CIS. The primary outcome was local recurrence‐free survival (RFS), which was estimated using the Kaplan–Meier method. Results: A total of 205 patients were identified. Treatment methods included circumcision, glansectomy, wide local excision, laser therapy and total glans resurfacing. Over a median (interquartile range [IQR]) follow‐up of 40 (26–65.6) months, there were 48 local recurrences, with 45.8% occurring in the first year and 81.3% occurring by year 5. The majority of recurrences were observed in the laser group (58.3%). The median (IQR) time to local recurrence was 15.9 (5.66–26.14) months. The 1‐ 2‐ and 5‐year RFS rates were 88.4, 85.6 and 75%, respectively, and the median (IQR) RFS time was 106.5 (80.2–132.2) months. Conclusions: Among patients with penile CIS selected for surgical management, durable responses at intermediate‐ to long‐term follow‐up were noted. For those with glandular CIS, glans resurfacing offered the best outcomes.